Reminiscence work in four dementia care settings in Ireland : the experience of the person with dementia and the facilitator - Parsons, Catherine Treena (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2015)
This thesis explores the experience of taking part in reminiscence work for people with dementia [PwD] and facilitators in Ireland. It focuses on four dementia care environments which are typical of the settings in which reminiscence is delivered - day care, respite care, acute hospital care and a nursing home. Interviews using semi-structured interview schedules were carried out with PwD taking part in reminiscence sessions and the facilitators carrying out the sessions. Family members who were available were also interviewed to provide additional, contextual material. Data from the resulting 21 interviews together with data from eight observations was analysed using Interpretative Phenomenological Analysis [I.P.A]. This thesis explores the benefits and challenges associated with delivering reminiscence work in realworld environments205, which may not always be ideal, and explores some of the environmental and organisational factors which can impinge on the reminiscence experience.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin